Improving documentation of visual acuity in patients suffering facial fractures. Issue 11 (26th November 2012) - Tahim, Arpan Singh; Bryant, Catherine; Greaney, Lisa; Rashid, Arif; Fan, Kathleen
Abstract : Failure to identify eye injuries associated with facial fractures can lead to life-altering morbidity. Oral and maxillofacial surgery teams receiving referrals of patients with these injuries have a vital role in ensuring that visual acuity (VA) is recorded at the time of presentation. We present a clinical audit of documentation of VA in 126 patients who sustained orbital floor and zygoma fractures. Our intervention involved a focussed teaching session for trainees responsible for taking such referrals. VA was appropriately documented in 16.5% before the session and 57.1% afterwards. This study shows that education of junior trainees gives rise to an increase in the proportion of patients where VA is properly documented. We suggest this teaching should occur routinely at junior doctor departmental inductions.